Risk factors and transitional probability of clinical events in Korean CKD patients using the multistate model - Ji Hye Kim; Jinheum Kim; Jayoun Kim; Ji Yong Jung; Jong Cheol Jeong; Seung Hyeok Han; Kook-Hwan Oh (Scientific Reports)
Abstract Korean chronic kidney disease (CKD) patients have relatively low cardiovascular disease (CVD) and high end stage kidney disease (ESKD) incidence rates. Using the multi-state model this study analyzed the 5- and 10-year cumulative hazard estimates, transition probabilities and risk factors associated with the five clinical transitions; ESKD, CVD, CVD to death, ESKD to death and death. CKD stages 1–4 patients from the KoreaN Cohort Study for Outcome in Patients With Chronic Kidney Disease cohort were included. Multivariable multi-state model analysis was performed to investigate the study outcomes associated with the five transitions. Among the 1502 patients (median age 54 years, male 61.3%), the overall prevalence of clinical events were: ESKD (22.6%), CVD (7.5%), death after ESKD (3.6%), death (3.3%) and death after CVD (1.2%). Patients who experienced intermediate ESKD event had higher risk of death than those who experienced CVD event (10-year cumulative hazard: 0.35; 95% CI: 0.23, 0.48 vs. 0.27; 95% CI: 0.15, 0.40). The 10-year transition probability was highest for enrollment to ESKD (0.27; 95% CI: (0.23, 0.31)) followed by enrollment to CVD (0.08; 95% CI: 0.07, 0.10). Different clinical risk factors were associated with each of the five transitions. Patients who experienced intermediate ESKD event were more exposed to death risk than those who experienced CVD and the highest 10-year progression probability was for enrollment to ESKD followed by death after ESKD. Different risk factors were associated with varying transitions. These findings correlate with the distinctive clinical features of Korean CKD patients.